ANALISIS PENGARUH E-RETAILING ATTRIBUTES TERHADAP E-SATISFACTION PADA SITUS BELANJA ONLINE BHINNEKA.COM DI SURABAYA - ALDIANTO, ARYO (Universitas Katolik Widya Mandala Surabaya, 2012)
E-retailing is a concept of marketing which is increasing these days as the result of the advanced information and technology. There are many companies which start to develop e-retailing. In order to develop or to create e-retailing, there are several things that should be considered; these things are known as e-retailing attributes. The function of e-retailing attributes is to give a positive impression so a customer can get satisfaction when the customer visits e-retailing. The purpose of this research is to know the relation between e-retailing attributes and e-satisfaction at the online shopping website bhinneka.com. E-retailing attributes consist of five attributes: shopping convenience, product selection, price, customization, and informativeness. The sample which is used for this research is all the customers of bhinneka.com in Surabaya. Purposive sample is applied for this research among 100 people as the total respondent. The method of data analysis which is used is a multiple linear regression analysis. The result of this research shows that shopping convenience, product selection, price, customization, and informativeness in e-retailing attributes give positive effects on e-satisfaction at the online shopping website bhinneka.com in Surabaya.